Effect of several humectants and potassium sorbate on the growth of Zygosaccharomyces bailii in model aqueous systems resembling low sugar products - Gliemmo, María Fernanda (2006)
The effect of solute type (glucose and polyols) and potassium sorbate (KS) level on the growth of Zygosaccharomyces bailii was evaluated in model aqueous systems resembling low sugar products. Growth curves were modeled using Gompertz equation. Parameters of the models were estimated and applied to analyze the effect of water activity (aw), solute used and KS on growth of Z. Bailii. It was observed that as KS concentration increased, the yeast growth diminished gradually. Use of polyols in the absence of KS generally decreased growth. In particular, xylitol was the solute that promoted the highest decrease in yeast growth. Depression of aw in the presence of KS produced different effects on growth rate depending on aw level, solute added and concentration of the preservative. In several cases, a synergism between humectants (glucose and polyols) and KS was observed in relation to growth inhibition. This behavior would allow to maintain the biological activity of the preservative diminishing the amount used.